Kajian Makna dalam Ilmu Semantik: Tinjauan Teoritis dan Klasifikasinya - Eri Ramadona; Aida Fitria (Jurnal Ilmiah Al-Furqan: Al-qur’an Bahasa dan Seni, 2025)
This study aims to examine the concept of meaning in semantics through a theoretical review and classification of meaning types, with a specific focus on the Arabic language. Employing a qualitative library research method, the study analyzes primary sources, including foundational works by prominent semanticists and relevant accredited journal articles. The findings reveal that meaning in Arabic is multidimensional, encompassing lexical, grammatical, denotative, connotative, idiomatic, and pragmatic meanings. High polysemy, variation between Classical (Fusha) and colloquial (‘Ammiyyah) Arabic, and theologically layered connotations necessitate a holistic semantic approach. These insights carry significant implications for Arabic language pedagogy, translation of religious texts, and the development of natural language processing technologies for Arabic. The study affirms that meaning cannot be understood in isolation from its linguistic, cognitive, and cultural contexts.